(untitled) (Vietnam Journal of Community Medicine, 2021)
A community intervention study with a placebo group, double-blind, evaluating the effect of using multi-micronutrient tablets on zinc deficiency, vitamin A deficiency among adolescent girls in mountainous high school in Thanh Hoa province in 2019 - 2020, using WHO and IZiNCG classifications. A double-blind randomized controlled trial was conducted among 322 school girls randomly divided into 2 groups. The multi-micronutrient supplements consist of 23 vitamins and minerals, including zinc (10.8 mg), vitamin A (550mcg), while the placebo group took a placebo tablet, once a week for 9 months. All of the children were dewormed by Albendazole 400 mg at baseline. Results showed that after 9 months of intervention, the mean serum zinc concentration of the intervention group (11.35 ± 2.88 µmol/l) was significantly improved and significantly higher than that of the Control group (10.51 ± 2.08 µmol/l) with p<0.05. The retinol concentration did not show significant difference between the two groups, but there was a significant improvement compared to the baseline time the intervention group with an increase level of 0.07 ± 0.30 mol. /l. After the intervention, the rate of zinc deficiency, sub-clinical vitamin A deficiency was not statistically significant between the two groups.